Mesenchymal stem cells-derived exosomes ameliorate high glucose and lipopolysaccharide-induced HPMECs injury through the Nrf2/HO-1 pathway - Hongyan Sun; Shitao Lu; Gaowei Qu; Junli Li; Bo Song (Taylor & Francis Group, 2023)
AbstractMesenchymal stem cells-derived exosomes (MSC-Exo) are considered to have great potential in the treatment of human diseases. However, the role of MSC-Exo in the process of diabetes with sepsis and the underlying molecular mechanism remain unclear. Human pulmonary microvascular endothelial cells (HPMECs) were treated with high glucose (HG) and lipopolysaccharide (LPS). Cell viability, migration, angiogenesis were analyzed by cell counting kit 8 assay, transwell assay and tube formation assay. Transmembrane electrical resistance (TER) detection and FITC-dextran assay were performed to evaluate cell barrier function. The protein levels of cell permeability-related markers, ferroptosis-related markers, exosomes-related markers, Nrf2 and HO-1 were examined using western bolt (WB) analysis. Besides, the levels of inflammation factors were tested by ELISA, and the levels of ferroptosis-related indicators were examined using corresponding assay kits. Flow cytometry was employed to analyze stem cell markers. The identification of MSC-Exo was performed using transmission electron microscopy, nanoparticle tracking analysis and WB analysis. DIO staining was used to examine the uptake of MSC-Exo by HPMECs. HG treatment suppressed HPMECs viability, migration, angiogenesis and TER, while promoted permeability, inflammation and ferroptosis. LPS treatment aggravated HG-induced HPMECs dysfunction, inflammation and ferroptosis. After HPMECs were co-cultured with MSC-Exo, cell injury induced by HG + LPS could be relieved. Moreover, MSC-Exo treatment enhanced the activity of Nrf2/HO-1 pathway in HG + LPS-induced HPMECs, and Nrf2-silenced MSC-Exo could promote HG + LPS-induced HPMECs injury. MSC-Exo alleviated HG + LPS-induced HPMECs injury via activating Nrf2/HO-1 pathway, confirming that it might be used for the treatment of diabetes with sepsis.